Historical variability and lifecycles of North Atlantic midlatitude cyclones originating in the tropics - Baker, Alexander J.; Hodges, Kevin I.; Schiemann, Reinhard K. H.; Vidale, Pier Luigi (Journal of Geophysical Research: Atmospheres, 2021)
North Atlantic tropical and post‐tropical cyclones impact midlatitude regions, but the inhomogeneous observational record of the latter stages of tropical cyclones precludes many climatological analyses. The frequency of tropical‐origin storms basin‐wide is projected to increase under anthropogenic climate change, so establishing confidence in our knowledge of their historical variability and lifecycles—against which climate model simulations may be evaluated—is important. We used a Lagrangian feature‐tracking algorithm to identify tropical cyclones that impacted Northeast North America and Europe in seven global reanalysis datasets, distinguishing systems that retained warm‐core structures or underwent warm seclusion from those that underwent extratropical transition, acquiring cold‐core, frontal structures. Over the last four decades, ∼25 % and ∼10 % of tropical‐origin cyclones made landfall across Northeast North America and Europe, respectively, as warm‐core systems, with, on average, higher wind speeds than cold‐core systems. Historical warm‐ and cold‐core landfalls also exhibit distinct tracks, likely responding to differing steering flow and midlatitude conditions.